Transcriptomic Analysis of Chloride Tolerance in Leptospirillum Ferriphilum Dsm 14647 Adapted to Nacl - Levican-Jaque, G; Chavez-Rosales, R; Rivera-Araya, J (Public Library of Science, 2022)
Chloride ions are toxic for most acidophilic microorganisms. In this study, the chloride tolerance mechanisms in the acidophilic iron-oxidizing bacterium Leptospirillum ferriphilum DSM 14647 adapted to 180 mM NaCl were investigated by a transcriptomic approach. Results showed that 99 genes were differentially expressed in the adapted versus the non-adapted cultures, of which 69 and 30 were significantly up-regulated or down-regulated, respectively. Genes that were up-regulated include carbonic anhydrase, cytochrome c oxidase (ccoN) and sulfide:quinone reductase (sqr), likely involved in intracellular pH regulation. Towards the same end, the cation/proton antiporter CzcA (czcA) was down-regulated. Adapted cells showed a higher oxygen consumption rate (2.2 x 10−9 ppm O2 s-1cell-1) than non-adapted cells (1.2 x 10−9 ppm O2 s-1cell-1). Genes coding for the antioxidants flavohemoprotein and cytochrome c peroxidase were also up-regulated. Measurements of the intracellular reactive oxygen species (ROS) level revealed that adapted cells had a lower level than non-adapted cells, suggesting that detoxification of ROS could be an important strategy to withstand NaCl. In addition, data analysis revealed the up-regulation of genes for Fe-S cluster biosynthesis (iscR), metal reduction (merA) and activation of a cellular response mediated by diffusible signal factors (DSFs) and the second messenger c-di-GMP. Several genes related to the synthesis of lipopolysaccharide and peptidoglycan were consistently down-regulated. Unexpectedly, the genes ectB, ectC and ectD involved in the biosynthesis of the compatible solutes (hydroxy)ectoine were also down-regulated. In line with these findings, although hydroxyectoine reached 20 nmol mg-1 of wet biomass in non-adapted cells, it was not detected in L. ferriphilum adapted to NaCl, suggesting that this canonical osmotic stress response was dispensable for salt adaptation. Differentially expressed transcripts and experimental validations suggest that adaptation to chloride in acidophilic microorganisms involves a multifactorial response that is different from the response in other bacteria studied. © 2022 Rivera-Araya et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited